An effective and rapid magnetic nanoparticle based dispersive solid phase extraction method for the extraction and preconcentration of cadmium from edible oil samples before ICP OES measurement - Oner, Miray; Bodur, Suleyman; Demir, Cansu; Yazici, Elif; Erarpat, Sezin; Bakirdere, Sezgin (ACADEMIC PRESS INC ELSEVIER SCIENCE, 2021)
In this study, a new and efficient sample pretreatment method called as dispersive solid phase extraction (DSPE) was proposed for the extraction and preconcentration of cadmium from edible oil samples and combined with inductively coupled plasma-optical emission spectrometry (ICP OES) for analyte determination at trace levels. Stearic acid coated-Fe3O4 magnetic nanoparticle (SA-MNP) was selected as the best adsorbent for the preconcentration of analyte. Under the optimum experimental conditions, analytical performance of DSPE-ICP OES system for the analyte was evaluated in terms of limit of detection (LOD), limit of quantification (LOQ) and dynamic range. LOD/LOQ values for sunflower oil/olive oil and hazelnut oil matrices were determined as 0.14/0.46 mu g/kg and 0.38/1.28 mu g/kg, respectively. In order to test the accuracy and applicability of DSPE-ICP OES method, recovery studies were performed in edible oils (sunflower oil, olive oil and hazelnut oil). The recovery results for sunflower oil, olive oil and hazelnut oil samples were calculated as 92.6-114.9 %, 85.0-104.3 % and 92.1-126.0 %, respectively.
Keywords: Cadmium; Dispersive solid phase extraction (DSPE); Edible oil; Inductively coupled Plasma-optical emission spectrometry (ICP OES); Magnetic nanoparticle (MNP); Stearic acid coated-Fe3O4; ATOMIC-ABSORPTION-SPECTROMETRY; OPTICAL-EMISSION SPECTROMETRY; ANODIC-STRIPPING VOLTAMMETRY; VEGETABLE-OILS; ONLINE PRECONCENTRATION; ENVIRONMENTAL-SAMPLES; FE3O4 NANOPARTICLES; FLOW-INJECTION; TRACE-ELEMENTS; METALS; Chemistry; Food Science & Technology